Investigation of processes leading to the decline of South Australia’s Caladenia species - Faast, Renate; Facelli, José (Lankesteriana: International Journal on Orchidology, 2015)
Of the 300 species of orchids recorded in South Australia, over one-third have been listed as vulner- able, rare, or endangered (Barker et al. 2005). While direct habitat loss is likely to be the major cause for reductions in the former ranges of species, indirect consequences of habitat fragmentation may be responsible for the continued decline of many species within remnant fragments.